FAKTOR- FAKTOR YANG MEMPENGARUHI TERJADINYA KATARAK PADA PETANI DI GARUT - Satria Tegar; Wahyu Budiana; Opep Cahya Nugraha (Akademi Refraksi Optisi dan Optometry Gapopin, 2022)
This study aims to determine the factors that influence the occurrence of cataracts in farmers in Garut. This research uses quantitative methods by observing and questionare. The population in this study were all farmers in Garut by taking a sample of 40 people. The result showed that cataracts occurred by factors, including aging (degenerative cataract) by 20%, not using eye protection when working by 85%, exposure to sun light with a long duration of 85% and lack attention to eye health by 75%.